EFEKTIVITAS PENGASAPAN MENGGUNAKAN KAYU KESAMBI (Schleichera oleosa) DIBANDINGKAN DENGAN BATOK KELAPA (Cocos nucifera) PADA DAGING BABI TERHADAP TPC, ORGANOLEPTIC DAN AWAL PEMBUSUKAN - Sheila Marty Yanestra; Junianto Wika Adi Pratama; Asih Rahayu; Patrianus Tomy (VITEK : Bidang Kedokteran Hewan, 2020)
The study was conducted to determine the effect of fogging using kesambi wood(Schleichera Oleosa) compared to coconut shells (Cocos Nucifera) in pork on TPC, organolepticsand early decay. The experimental design used was a completely randomized design with fourtreatments with a total of six replications. The treatments applied were P1 fogging for 30 minutesusing wood kesambi (Scheleichera Oleosa), P2 fogging for 30 minutes using coconut shells (CocosNicifera), P3 fogging for 45 minutes using kesambi wood (Scheleichera Oleosa), P4 fogging for 45minutes using coconut shells (Cocos Nicifera), P3 fogging for 45 minutes using wood cage(Scheleichera Oleosa), P4 fogging for 45 minutes using coconut shells (Cocos Nicifera), P3 foggingfor 45 minutes using wood cage (Scheleichera Oleosa), P4 fogging for 45 minutes using coconutshells (Cocos Nicifera), P3 fogging for 45 minutes using wood cage (Scheleichera Oleosa) coconut(Cocos Nucifera). The results of the analysis of total plate count (TPC) showed that there was noreal difference. The results of the color and taste organleptic analysis showed that there was nosignificant difference between P1, P2, P3 and P4 where P ˃ 0.05, while the texture and aroma testshowed significant changes between P1, P2, P3 and P4 where P ˂ 0.05. In the initial decay testshowed that p1 had the lowest positive results of the initial decay test that is 1 positive sample froma total of 6 samples.